At the Cutting Edge of the Impossible: A Tribute to Vladimir P. Demikhov - Konstantinov, Igor E. (Texas Heart Institute, 2009)
Vladimir P. Demikhov (1916–1998) performed the world's first experimental intrathoracic transplantations and coronary artery bypass operation. His successes heralded the era of modern heart and lung transplantation and the surgical treatment of coronary artery disease. Even though he was one of the greatest experimental surgeons of the 20th century, his international isolation fueled speculation, suppositions, and myths. Ironically, his transplantation of a dog's head drew more publicity than did his pioneering thoracic surgical accomplishments, and he became an easy target for criticism. An account of Demikhov's life and work is presented herein.